Ethnobotanical study of medicinal plants in the Hawassa Zuria District, Sidama zone, Southern Ethiopia - Banchiamlak Nigussie Tefera; Young-Dong Kim (BMC, 2019)
Abstract Background Ethiopia is one of the species-rich countries in the world and the center of origin with regard to the diversity of many plant species. Ethnobotanical studies are vital to investigate these diverse biological resources for medicinal purposes. The aim of this study was to document the indigenous knowledge of the Sidama people regarding the use of medicinal plants to treat human and livestock diseases in the Hawassa Zuria district of Southern Ethiopia. Methods A total of 150 informants (118 men and 32 women) were selected to collect ethnobotanical information from ten kebeles by means of a stratified purposive sampling method. Among the informants, 30 key informants were selected purposefully. Ethnobotanical data were collected through semi-structured interviews and group discussions and were analyzed by descriptive statistics, informant consensus factor (ICF), fidelity level (FL), and ranking methods. Results A total of 105 medicinal plants distributed across 52 families and 96 genera were collected. Fabaceae (11 species) was represented by the highest number of plant species, followed by Lamiaceae (7 species). Herbs (34%) were the dominant growth habits, followed by trees (33%). Leaves (56%) were the dominant plant part used in the preparation of remedies, followed by fruit (15%). The most common method of remedy preparation was grinding (39%) followed by chewing and boiling (11% each). Oral (74%) was the major routes of administration, followed by dermal (20%). There was a significant knowledge difference (p < 0.05) between social groups regarding the use of traditional medicinal plants. Insects and ectoparasites disease category (0.95) had higher informant consensus factor value followed by fever disease category (0.91). Eucalyptus globulus Labill. (100%) had a higher fidelity level to treat stomachache, followed by Ensete ventricosum (Welw.) Cheesman. (87.27%) to treat placenta delay. Ensete ventricosum (total score = 73) was ranked highest as the most preferable medicinal plant for various purposes by local people, followed by Olea welwitschii (Knobl.) Gilg (total score = 72). Conclusion The present study revealed the existence of indigenous knowledge of medicinal plants to treat human and livestock ailments. However, agricultural expansion, firewood collection, environmental degradation, and deforestation are the main threats to medicinal plants. Therefore, there should be mentoring for the local people in the study area to conserve their indigenous knowledge resources and prevent the extinction of medicinal plants.